EVALUATION OF ANTIOXIDANT, ANTIMICROBIAL, AND ANTIFUNGAL POTENTIAL OF CUCURBITA PEPO VAR. FASTIGATA SEED EXTRACTS - RS SONI, ROSHNI; BALI, MANOJ (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The current study aims to study the antioxidant and antimicrobial and antifungal potential of the methanolic extract of Cucurbita pepo var. fastigata seeds (MECS). Methods: Extraction of the seeds has been carried out with solvents of increasing polarity (chloroform, acetone, and methanol) and the phytochemical study of the methanolic extract have been carried out using standard methods. The free radical scavenging activity of all the extracts was evaluated by DPPH and H2O2 methods. Standard disk diffusion method was used to evaluate antibacterial and antifungal activities. Results: Phytochemical evaluation showed the maximum presence of triterpenoids, phenolic compounds, tannins and small amount of Coumarins. Methanolic extract revealed momentous antioxidant activity as compared to chloroform and ethyl acetate extract. Hence, methanolic extract of C. pepo. seeds (MECS) at a dose level of 100, 200 and 300 μg/ml was evaluated for antioxidant potential. Maximum free radical scavenging activity of methanolic seed extract of cucurbita pepo var. fastigata has been found at a dose of 300 μg/ml to be 63±0.16 % by 1,1-diphenyl-2-picryl hydrazyl model and at a value of 78% at 300 μg/ml with H2O2 model. Methanolic extract also showed the presence of antibacterial activity. Conclusion: Presence of phytochemicals in the methanolic extract is responsible for the antioxidant potential. Extracts were investigated for antibacterial activity using the standard disc diffusion assay method against Bacillus subtilis, Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa and for the antifungal activities against Aspergillus niger and Candida albicans. The seed extract showed the presence of antibacterial activity, but the antifungal activity was found to be absent in the extract.